Acoustic Radiation Patterns of Different Polygon Piston Surfaces - Yusuf, Taofeek Ayotunde; Aodu, Sheriff Abiodun; Alabi, Abeeb Opeyemi (Acta Polytechnica, 2024)
Transducers are used in acoustic remote sensing and several other modern applications. The radiating surface geometry of a single acoustic transducer affects its beam pattern and has a cumulative effect on the overall performance of an array configuration. In addition, the transducers with polygon radiating surfaces provide more compact structure in an array than the circular pistons due to their flat surface edges. However, until now, the radiation patterns of acoustic polygonal pistons have not been exclusively studied and documented. In this study, the directional factors of acoustic pistons with polygonal surfaces of three to ten sides were derived analytically from the first principle using the Rayleigh integral. These directional factors were used to synthesise and characterise the radiation patterns of the piston sources in comparison with the baffled circular piston of an equivalent surface area. The rectangular, the triangular, and the rest of the polygons have the same performance with the circular piston when the surface diameter is not higher than 0.5λ, 0.28λ and 0.43λ, respectively. The main lobe of the acoustic emissions from the square is very close to that of the circular piston whose diameter is greater than a wavelength while that of the rectangle is wider. The results show that the radiating surface perimeter and symmetry are the two most critical factors affecting the beam characteristics of a piston source rather than the surface area or the number of sides. The theoretical results were validated using the finite element method with an excellent compliance.